Eino and Elisa: Contextual Christianity Discusses Urban Sustainability - Kjellberg, Seppo (Journal for the study of religion, nature and culture, 2004)
In a recent Finnish qualitative study on urban sustainability it became evident that two devoted lay Christians held totally opposite opinions on the subject. One defended an anthropocentric viewpoint on the basis of the Hebrew Bible idea of humans being made in the image of God, while the other used the same text to defend an ecocentric view of environmentally responsible humans. Within the context of the Finnish State Church, both views can—without attracting attention—live side by side as Christian answers to the demand for sustainable city planning. However, a paradigm transition towards a more holistic view of the environment seems to be forthcoming. I would suggest that a culture of dialogue, both between Christians themselves and between Christians and people holding a different world-view, would lead to better self-understanding and to an ability to use the best of the Christian heritage for the development of a holistically understood ecological city. In order to be a truly liberating theology, urban ecotheology has to be openly discursive. To understand this, the alternative models for a contextual theology espoused by Sallie McFague are especially helpful.